Isolation and Identification of a Recombinant Porcine Epidemic Diarrhea Virus With a Novel Insertion in S1 Domain - Li, Dongliang; Li, Yongtao; Liu, Yunchao; Chen, Yumei; Jiao, Wenqiang; Feng, Hua; Wei, Qiang; Wang, Jucai; Zhang, Yuhang; Zhang, Gaiping (Frontiers in Microbiology, 2021)
Porcine epidemic diarrhea virus is the major pathogen that causes diarrhea and high mortality in newborn piglets with devastating impact to the pig industry. Recombination and mutation are the main driving forces of viral evolution and genetic diversity of PEDV. In 2016, an outbreak of diarrhea in piglets occurred in an intensive pig farm in Central China. A novel PEDV isolate (called HNAY) was successfully isolated from clinical samples. Sequence analysis and alignment showed that HNAY possessed 21-nucleotide (nt) insertion in its S1 gene, which has never been reported in other PEDV isolates. Moreover, the sequence of the insertion was identical with the sequence fragment in PEDV N gene. Notably, the HNAY strain exhibited two unique mutations (T500A and L521Y) in the neutralizing epitopes of the S1 protein that were different from those of other PEDV variant strains and CV777-based vaccine strains. Additionally, PEDV HNAY might be derived from a natural recombination between two Chinese variant PEDV strains. Animal experiments demonstrated that HNAY displayed higher pathogenicity compared with two other clinical isolates. This study lays the foundation for better understanding of the genetic evolution and molecular pathogenesis of PEDV.